DİABETİK NEFROPATİYE GENETİK YATKINLIKTA ADDUCİN GLY460TRP, ACE I/D VE AGT M235T GEN POLİMORFİZMLERİNİN ROLÜ - SANCAKDAR, ENVER (Fırat Üniveristesi, 2010)
Diabetes mellitus (DM), yaşam boyu sürekli izlem ve tedavi gerektiren, akut ve kronik komplikasyonları ile yaşam kalitesini azaltan morbiditesi ve mortalitesi yüksek kronik metabolik bir hastalıktır. WHO`a göre, yaklaşık 170 milyon DM hastası bulunmaktadır. DM sıklığındaki ve yaşam süresindeki artışa bağlı DNP sıklığı da artmaktadır. Diyabetiklerin %20-40'ında proteinüri ve bunların %10-50'sinde SDBY gelişmektedir.Genetik, polyol yolu aktivasyonu, PKC aktivasyon, ekstrasellüler matriks bozuklukları ve RAAS aktivasyonu DNP gelişiminde etkilidir. ACE I/D polimorfizminden I-alleli, AGT M235T'den T-alleli ve ADD G460W'den W-allel varlığının DNP'ye yatkınlık oluşturduğu ileri sürülmektedir. Çalışmamızda diyabetli kişilerin, DNP'ye gidişlerinde, AGT M235T, ACE I/D ve ADD G460W polimorfizmlerinin etkisini incelemek amaçlanmıştır. Kontrol grubu olarak 100 DM'li hasta, çalışma grubu olarak 194 nefropatili hasta incelendi.ACE I/D polimorfizminin DD genotipi %54.0 (p=0.003) ve D alleli %69.0 (p<0.0001) diyabetik grupta, nefropatili grupta ise ID, II genotipi sırası ile 78(%40.2) ve 51(%26.3) (p=0.003) ve I alleli %46.4 (p<0.0001) ile I allelinin varlığı nefropati ile ilişkiliydi. Gruplar arasında AGT M235T ve ACE I/D polimorfizminin birlikteliğinde; genotipler arasında anlamlılık yokken(p=0.055), M/D allelleri ( %42) diyabetik; T/I allelleri ( %28.1) nefropatik grupta anlamlıydı (p=0.004). Tek başına ADD G460W polimorfizminde GG (%77.3) ve WW (%7.7) genotiplerinin (p=0.025) nefropatiye yatkın olabileceği, ACE I/D birlikteliğinde; diyabetik grupta DD/GG (%45); DNP'li grupta ID/GG (%29.9) ve II/GG ( %19.6) birlikteliği anlamlıydı (p=0.006). D/G ( %64) allelleri diyabetik; I/G allelleri ise (%36.6) DNP'li grupta anlamlıydı (p=0.003).Sonuç olarak; diyabetik hastalarda nefropatiye olan yatkınlıkta; ACE-ADD birlikteliğinde II-ID/GG genotip ile I/G allellerinin ve ACE-AGT birlikteliğinde ise TT/ID genotipi ile T/I allellerinin etkili olabileceğini düşünmekteyiz.Anahtar Kelimeler: DM, Diyabetik Nefropati, ACE I/D polimorfizmi, AGT M235T polimorfizmi, ADD G460W polimorfizmi

Diabetes mellitus is a metabolic disease with a high incidence of morbidity and mortality lowering the quality of life with acute and chronic complications and it needs to be followed up and treated throughout the lifespan. There are 170 million diabetes mellitus patients according to the WHO. Concordant with the frequency of DM and the increase in the length of life frequency of DNP is also increased. 20%-40% of the diabetic patients end up with proteinuria and in 10%-50% among these patients SDBY is developed.Genetic, polyol route activation, PKC activation, extracellular matrix deterioration and RAAS activation are effective on the development of DNP. The I allele of the ACE I/D polymorphism, AGT M235T?s T allele and ADD G460W?s W allele presence are purported to present a predisposition to DNP. In our study we aimed to investigate the effect of the AGT M235T, ACE I/D and ADD 460W polymorphisms in the development of DNP in patients with diabetes mellitus. The study group consisted of 194 patients with Diabetic nephropathy and the control group contained 100 DM patients.In the diabetic group the DD genotype of the ACE I/D polymorphism was 54 (54.0%) (p=0.003) and the D allele was 69.0% (p<0.0001) and in the nephropathy group II genotype of the ID were 78 (40.2%) and 51 (26.3%) (p=0.003) and the I allele was 46.4 (p<0.0001) respectively and the presence of the I allele was associated with the presence of nephropathy. There was no significance between the genotypes in the presence of a coexistence of AGT M235T and ACE I/D polymorphisms between the groups (p=0.055) the MD alleles (42%) demonstrated significance in the diabetic and the T/I alleles (28.1) demonstrated significance in the nephropathy group (p=0.0004). In the ADD G640W polymorphism on its own, subjects having GG (77.3%) and WW (7.7%) genotypes (p=0.025) might have been predisposed to nephropathy however when in combination with the ACE I/D, the presence of the DD/GG (45%) in the diabetic group and the presence of the ID/GG (29.9%) and II/GG (19.6%) combination in the DNP group were statistically significant (p=0.006). The D/G (64%) alleles were significant in the diabetic and the I/G (36.6) alleles were significant in the DNP groups respectively (p=0.003).As a conclusion we think that the II-ID/GG genotype and the I/G alleles in the presence of the ACE-ADD combination and TT/ID genotype and T/I alleles in the ACE-AGT combination may be effective in the predisposition of the diabetic patients to nephropathy.Key Words: DM, Diabetic nephropathy, ACE I/D polymorphism, AGT M235T polymorphism, ADD G460W polymorphism.
The role of adducin GLY4460TRP, ACE I/D and AGT M235T gene polymorphisms onthe genetic predisposition to diabetic nephropathy
Keywords: Biyokimya; Genetik